Compositional and nutritional value of lupin cultivars: Identifying high-protein seeds for enhanced protein isolate production and phytochemical valorisation - Pau Taberner-Pibernat; Albert Ribas-Agustí; Gisela Quinteros; Gerard Sabeña; Miguel López-Gómez; Rubén Domínguez-Valencia; Ricard Bou (Journal of Agriculture and Food Research)
The rising global demand for sustainable protein sources has increased the interest in legumes, particularly lupin, due to its nutritional and technological advantages. Beyond the high protein content, some phytochemicals in lupin seeds such as quinolizidine alkaloids (QAs), saponins, phytic acid, and total phenolic compounds (TPC) warrant further exploration due to their potential for valorisation following a seed protein isolation process, offering opportunities for their use in functional foods, nutraceuticals, or other high-value applications. This work evaluated eight cultivars from different cultivated lupin species —L. albus (Estoril, Celina, and Frieda), L. angustifolius (Giribita and Carabor), and L. luteus (Acos, Cardiga, and a commercial mixture)— in Europe as alternative protein sources. Each cultivar was assessed in terms of proximate composition, phytochemical content, and protein extraction yield. The findings revealed significant inter- and intra-species variability in protein, total dietary fibre, and fat content among the studied cultivars. Lupin protein profile was found to be particularly rich in essential amino acids, including leucine and lysine, as well as beneficial unsaturated fatty acids across all evaluated cultivars. The studied phytochemicals, especially quinolizidine alkaloids, vary significantly among species, while cultivars within the same species showed a more consistent profile. The wet extraction process yielded high-purity protein isolates with favourable extraction efficiency. These findings highlight the potential of lupin for diverse applications in the food and industrial sectors. Cultivar selection is essential to enhance protein extraction yields and colour, as well as to consider lupin as a source of various phytochemicals for valorisation.